Reversal of albuminuria by combined AM6545 and perindopril therapy in experimental diabetic nephropathy. (6th November 2018) - Barutta, F; Bellini, S; Mastrocola, R; Gambino, R; Piscitelli, F; di Marzo, V; Corbetta, B; Vemuri, VK; Makriyannis, A; Annaratone, L; Bruno, G; Gruden, G
Abstract : Background and Purpose: The endocannabinoid (EC) system has been implicated in the pathogenesis of diabetic nephropathy (DN). We investigated the effects of peripheral blockade of the cannabinoid CB1 receptor as an add‐on treatment to ACE‐inhibition in type 1 diabetic mice (DM) with established albuminuria. Experimental Approach: Renal functional parameters (albumin excretion rate, creatinine clearance), tubular injury, renal structure, both EC and CB receptor levels and markers of podocyte dysfunction, fibrosis and inflammation were studied in streptozotocin‐induced DM treated for 14 weeks with vehicle, the ACE‐inhibitor perindopril (2 mg·kg −1 ·day −1 ), peripherally‐restricted CB1 receptor antagonist AM6545 (10 mg·kg −1 ·day −1 ) or both. Treatments began at 8 weeks after diabetes onset, when early DN is established. Key Results: CB1 receptors were overexpressed in DM and neither perindopril nor AM6545 altered this effect, while both drugs abolished diabetes‐induced overexpression of angiotensin AT1 receptors. Single treatment with either AM6545 or perindopril significantly reduced progression of albuminuria, down‐regulation of nephrin and podocin, inflammation and expression of markers of fibrosis. However, reversal of albuminuria was only observed in mice administered both treatments. The ability of the combination therapy to completely abolish slit diaphragm protein loss, monocyte infiltration, overexpression of inflammatory markers and favour macrophage polarization towards an M2 phenotype may explain this greater efficacy. In vitro experiments confirmed that CB1 receptor activation directly inhibits retinoic acid‐induced nephrin expression in podocytes and IL‐4‐induced M2 polarization in macrophages. Conclusion and Implications: Peripheral CB1 receptor blockade used as add‐on treatment to ACE‐inhibition reverses albuminuria, nephrin loss and inflammation in DM.